2010
DOI: 10.1051/0004-6361/201014950
|View full text |Cite
|
Sign up to set email alerts
|

On the observability of T Tauri accretion shocks in the X-ray band

Abstract: Context. High resolution X-ray observations of classical T Tauri stars (CTTSs) show a soft X-ray excess due to high density plasma (n e = 10 11 −10 13 cm −3 ). This emission has been attributed to shock-heated accreting material impacting onto the stellar surface. Aims. We investigate the observability of the shock-heated accreting material in the X-ray band as a function of the accretion stream properties (velocity, density, and metal abundance) in the case of plasma-β 1 (thermal pressure magnetic pressure) i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
120
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 59 publications
(127 citation statements)
references
References 49 publications
(87 reference statements)
7
120
0
Order By: Relevance
“…As discussed below, the evolution of the accretion shock and of the postshock plasma is analogous to that described in Paper I when the magnetic field is weak (β > ∼ 1 in the postshock plasma; run B50-D11-Unif) and to that described by Sacco et al (2010) in the limit of strong magnetic field (β 1; run B500-D11-Unif). Figure 2 shows maps of temperature, density, and β for runs B50-D11-Unif and B500-D11-Unif at the labeled times.…”
Section: The Reference Case: Uniform Magnetic Fieldsupporting
confidence: 53%
See 2 more Smart Citations
“…As discussed below, the evolution of the accretion shock and of the postshock plasma is analogous to that described in Paper I when the magnetic field is weak (β > ∼ 1 in the postshock plasma; run B50-D11-Unif) and to that described by Sacco et al (2010) in the limit of strong magnetic field (β 1; run B500-D11-Unif). Figure 2 shows maps of temperature, density, and β for runs B50-D11-Unif and B500-D11-Unif at the labeled times.…”
Section: The Reference Case: Uniform Magnetic Fieldsupporting
confidence: 53%
“…In the present study, we restrict our analysis to accretion stream impacts that are able to produce detectable X-ray emission. Sacco et al (2010) have shown that X-ray observations preferentially reveal emission from the impact of low density (n str0 < ∼ 10 12 cm −3 ) and high velocity (|u str0 | > ∼ 300 km s −1 ) accretion streams due to the large absorption of dense postshock plasma. X-ray observations show that the above requirements are fitted, for instance, in the well-studied young accreting star MP Mus (Argiroffi et al 2007) which is an ideal test case for our analysis.…”
Section: Mhd Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent hydrodynamical simulations (Sacco et al 2008;2010) have demonstrated that, even if the post-shock zone is not stationary (and characterized by quasi-periodic shock oscillations), the time-averaged properties of the post-shock zone are, in general, well-described by the stationary model. Sacco et al (2010) have also shown that the higher the post-shock temperature the larger the discrepancies between the stationary and the hydrodynamical models. This is mainly due to the fact that the thermal conduction (which is not taken into account in the stationary model and that is more efficient for higher post-shock temperatures) drains energy from the shock-heated plasma to the chromosphere through a thin transition region, and acts as an additional cooling mechanism (see also Orlando et al 2010).…”
Section: X-ray Data Analysismentioning
confidence: 91%
“…From a theoretical point of view, it has been debated whether X-rays emitted by shock-heated plasma in CTTS are able to escape from the shock region, and hence be detected (Drake 2005;Sacco et al 2010). Their escape probability depends on the height of the shock surface in the stellar atmosphere and on the direction of emission.…”
Section: High Density Cool Plasma and Accretion Shock(s)mentioning
confidence: 99%